SUSTAINABILITY OF THE AGE-OLD BELL METAL CRAFT: CAN MARKET ORIENTATION BE THE GAME- CHANGER? - Dutta, Monalisha; Chanu, Ayekpam Ibemcha (International Journal of Research -GRANTHAALAYAH, 2025)
The sustainability of any craft form cannot be thought of without considering the economic security of the artisan community. This depends to a large extent on their behaviour in understanding the different market participants to stay informed about the market dynamics. The present study examines the various challenges faced by the bell metal industry in Assam, which is one of the traditional craft forms practised by artisans for several decades. It also highlights how the different dimensions of Market Orientation as evidenced from the extant literature can help in mitigating those problems and help in achieving sustainability. The present study is based on both primary and secondary data. The findings reveal that incorporating different dimensions of market orientation into the different stages of operation in the bell metal industry helps with positive outcomes like: regular production, improved productivity, more goodwill, a larger customer base, financial assistance, boosting connectivity, etc. which would in turn contribute towards increased revenue of the industry and subsequently ensure the sustainability of the bell metal craft.